Meta inflação: uma nova abordagem para a política monetária - Mathias, Alexandre da Cunha (1998)
This study presents a new approach for conducting monetary policy: inflation targeting. The survey begins with a historical review of the recent literature on monetary economics from the Phillips Curve and an analysis of the classical options for monetary policy to a careful description of the new framework. The practice experiences of Germany, New Zealand, Canada and England are analyzed. The impacts of the new regime on the inflation inertia process in examined with time series techniques. The study finds that inflation targeting increases monetary discipline and makes monetary policy more coherent and transparent.